One, two, ah-choo! - Farber, Erica (Richard Scarry's great big schoolhouse readers., 2013)
When Sally Cat, Mr. and Mrs. Cat, and everyone at school come down with colds, Huckle and Lowly take care of their ailing friends in messy, silly ways that culminate in two more sick patients by the end of a busy day.